Perencanaan Kebijakan Persediaan Vaksin Booster Dengan Metode Continuous Review (s,S) Untuk Mengurangi Overstock Di Rumah Sakit Tentara Kota Pematangsiantar - Renata Hany; Nerli Khairani (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
Pematangsiantar City Army Hospital is one of the state-owned health facilities that provides booster vaccination services with 4 types of booster vaccines available, namely sinovac, astrazeneca, pfizer and moderna. The uncertain level of demand for booster vaccines causes the Pematangsiantar City Army Hospital to require booster vaccine inventory policy planning using the continuous review (s,S) method to prevent overstock which results in considerable cost expenditures. From the calculation of booster vaccine inventory control using the continuous review method (s,S), it is obtained that the total inventory cost has a significant percentage change. For the type of sinovac, the percentage change in total inventory costs reaches 92% of the total inventory costs in the existing conditions, for astrazeneca reaches 58% of the total inventory costs in the existing conditions, for pfizer reaches 60% of the total inventory costs in the existing conditions, and for moderna reaches 95% of the total inventory costs in the existing conditions. The results of the calculation of the total cost of inventory with continuous review (s,S) can provide a decrease in costs incurred by the Pematangsiantar City Army Hospital. This is because the continuous review (s,S) inventory policy minimises the cost of vaccine shortages which are quite costly.